The Evolution of Fabrication Methods in Human Retina Regeneration - Beatrice Belgio; Anna Paola Salvetti; Sara Mantero; Federica Boschetti (Applied Sciences, 2021)
Optic nerve and retinal diseases such as age-related macular degeneration and inherited retinal dystrophies (IRDs) often cause permanent sight loss. Currently, a limited number of retinal diseases can be treated. Hence, new strategies are needed. Regenerative medicine and especially tissue engineering have recently emerged as promising alternatives to repair retinal degeneration and recover vision. Here, we provide an overview of retinal anatomy and diseases and a comprehensive review of retinal regeneration approaches. In the first part of the review, we present scaffold-free approaches such as gene therapy and cell sheet technology while in the second part, we focus on fabrication techniques to produce a retinal scaffold with a particular emphasis on recent trends and advances in fabrication techniques. To this end, the use of electrospinning, 3D bioprinting and lithography in retinal regeneration was explored.